ANALYSING THE MACROORGANISATIONAL STRUCTURE OF THE REVIEW ARTICLE GENRE IN APPLIED LINGUISTICS - AZAR, Ali Sorayyaei; HASHIM, Azirah (Issues in language studies, 2017)
The aim of this research is (1) to analyse the macro-organisational structure and (2) to investigate and describe the analytical sections of the data. The data, drawn from a randomly selected corpus of 32 review articles, was analysed following Swales’ (1990) genre analysis to describe and investigate the schematic structure of the review article genre. The findings revealed that the CARS model was often observed in this genre. Moreover, although both review articles and research articles have been considered sub-genres of the research genre, there is a significant variation among them in terms of the schematic structure, rhetorical strategies, and functions. The schematic structure and functions of the review article genre were further investigated by consulting the specialist informants. The macroorganisational structure of this genre proposed hence provide the instructive guidance for EFL graduates and junior researchers how to review the developments critically during their research writing. Keywords: academic review genres, review article genre, macro-organisational structure, analytical sections of review article genre